Promotion demand forecast: A case study of Coca Cola Enterprise. - Lai, Hoi-Yin Cecilia (2007)
In this highly competitive business environment, forecasting becomes one of the hot topics. Every business organization uses forecasts for decision marking. Forecasting can help companies to determine the market strategy. It also helps in production planning and resources allocation. A good forecast can help the management team to make the best decision. Nowadays, it is important to develop a collaborative partnership within the supply chain. Coca Cola Enterprise (CCE) is working with its customers to develop the collaborative partnership. The relationship enhances the companies within the supply chain to obtain the great benefit. This project aims at helping to improve its current forecast process. This project aims at reducing the time consumption on the forecast process and increasing the accuracy of the forecasts. 72 forecasts models have been created by using Excel Data Analysis. The best model of each individual product is selected. However, the fitness of each model varied. The reason of the difference will be studied in this project. A high accuracy forecast enhances the relationship between CCE and its customers. Intangible benefit, such as better shelf availability, can be obtained. Hence, both companies can be benefited.